Analysis of Consumer Buyer Decisions at Lazatto Tasikmalaya - Wakil, Muhamad Abdul (Universitas Mercu Buana, 2026)
Buyer decisions are a key factor in determining the sustainability of a business because they are directly related to the level of sales, satisfaction, and consumer loyalty. In the increasingly competitive culinary business, companies are expected to be able to understand the various factors that influence buyer decisions so they can maintain their existence and increase their competitiveness. Lazatto Tasikmalaya, as a fast food business, needs to understand the level of consumer buyer decisions and how consumers respond to product quality and the level of satisfaction they feel. Understanding these aspects is an important basis for formulating strategies to improve product and service quality in order to create sustainable customer loyalty.